Application of Rasnadi Churnam on Shiras (Mid- Scalp) as a Daily Regimen (International Journal of Ayurveda and Pharma Research, 2024)
In all the Ayurveda classics there are several practices which are having specific benefits have been mentioned to be followed daily and seasonally to maintain the health of a healthy individual. There are traditional practices which have been followed by people in particular region those are having classical references and without too. One among those traditional practice is application of Rasnadi churnam over wet mid-scalp after daily bath as a part of Dinacharya (daily regimen) to prevent seepage of water into the sinuses thus preventing infection, which has been given under Churna yoga (powder formulation) in the classical Ayurveda text from Kerala named Sahasrayogam as the name indicates it contain more than thousand formulations those are highly useful in various ailments. This article aims to generalize these kinds of practices to other societies so that everyone can adopt these kind of traditional Ayurveda practices in their daily life.